Structural, elastic and optical properties of zinc tellurite glass system doped with samarium, samarium nanoparticles and silver oxide - Abubakar, Tafida Rabiu (2021)
Four series of zinc tellurite glasses doped with samarium, samarium nanoparticles and silver oxide were successfully fabricated using the conventional melt-quenching technique. The glasses were prepared based on the empirical formulas of [(TeO2)0.7 (ZnO)0.3[1-x [Sm2O3/ Sm2O3Nps]X, where x = 0.01 to 0.05 molar fraction and [{(TeO2)0.7 (ZnO)0.3}0.99 (Sm2O3/ Sm2O3Nps)0.01]1-y (Ag2O) y, with y = 0.005 to 0.025 molar fraction. The XRD tests confirmed that the glasses are amorphous. The Fourier Transform Infrared Spectrometer (FTIR) showed that all the glasses have a structural unit of TeO4 and TeO3. The TEM-images confirmed the existence of samarium nanoparticles with particle size of about 72.43 nm. The density of Sm2O3 and Sm2O3 NPs increased from 5.0419 to 5.3005 g/cm3 and from 5.1095 to 5.3286 g/cm3. Meanwhile, the molar volume increased from 27.4238 to 27.6901 cm3/mol, and from 27.0610 to 27.5441 cm3/mol. For Ag2O(Sm) glasses the density increased from 5.1999 to 5.3747 g/cm3 and decreased for Ag2O (Sm NPs) from 5.3162 to 4.9163 g/cm3.The molar volume decreased from 26.6788 to 26.1590 cm3/mol for Ag2O(Sm) and increased from 26.0952 to 28.5981 cm3/mol for Ag2O (Sm NPs) glasses. The elastic moduli and other elastic parameters increase with increase in dopant while the values of Poisson’s ratio lie in the range of 0.2734 to 0.2902. The direct and indirect optical band gap increased from 2.7855 eV to 2.9867 eV and from 2.6714 eV to 3.0676 eV for Sm2O3 and Sm2O3 NPs doped series. Similarly, Eopt increased from 2.9691 eV to 3.1054 eV and from 2.7417 eV to 2.6278 eV for Ag2O (Sm) and Ag2O (Sm NPs). Photoluminescence investigation reveals that the glass samples can be used as a laser active medium for emission at 605 and 607 nm wavelength corresponding to the 4G 5/2 to 6H 7/2 transitions. The Judd-Offelt analysis reveals that the large values of gain bandwidth (4.427x 10-21), optical gain (5.199 x10-25) and the radiative transition probabilities [(16195 S-1)/ (15894 S-1)] can be used for laser application. Furthermore, Ag2O (Sm NPs) doped series having the largest value of gain bandwidth (9.975x 10-21), optical gain (9.061 x10-25) and the radiative transition probabilities [(119021 S-1)/ (16832 S-1)] made it the best candidate for laser materials. Therefore, this research contributes to addressing the pressing challenge of developing new materials for laser.